Bentonite blended with bagasse ash as an adsorbent for reactive red 198 dyes. Issue 1 (24th December 2021) - Adane, Teshale; Adugna, Amare Tiruneh; Alemayehu, Esayas
Abstract: Adsorption offers an efficient, cost-effective, and eco-friendly method for the treatment of dye-laden wastewater. This work presents reactive red 198 (RR198) removal by adsorption using bentonite clay (BC) blended with sugar cane bagasse ash (SCBA). The adsorbent's surface morphologies, crystalline phase structures, functional groups, and specific surface before and after adsorption were examined using SEM, XRD, FTIR, and BET respectively. Central composite design (CCD) under response surface methodology (RSM) was applied to optimize independent and dependent variable values. The optimal parameters for RR198 removal using the blended adsorbent were 107 minutes contact time, 0.934 g/L adsorbent dose, and 15 mg/L initial dye concentration, and 85.2% RR198 removal efficiency was achieved. The sorption isotherms and kinetics were evaluated using various existing models. The Freundlich isotherm model (R 2 = 0.95) and the pseudo-second-order equation best described the adsorption parameters and the RR198 adsorption kinetic mechanism, respectively. Desorption and reusability experiments in batch study confirmed that BC blended with SCBA can be used multiple times for dye removal from wastewater. HIGHLIGHTS: Bentonite blended with SCBA as adsorbent removed RR198 from synthetic solution successfully. The highest RR 198 removal efficiency from water was at pH 2. CCD under RSM was applied to determine optimal parameters of independent and dependent variables. Graphical Abstract